Stressors related to the COVID-19 pandemic and their association with distress, depressive, and anxiety symptoms in cancer out-patients - Frank, Tamara; Pichler, Theresia; Maier, Sabrina; Batenhorst, Ineke; Abawi, Tanja; Harbeck, Nadia; Algül, Hana; Heinemann, Volker; Hermelink, Kerstin; Mumm, Friederike; Dinkel, Andreas (Frontiers in Psychology, 2023)
Patients with cancer might be particularly prone to stress caused by the COVID-19 pandemic. The aim of this study was to investigate the impact of pandemic-related stressors on oncological patients’ psychological well-being. During the second wave of the COVID-19 pandemic in Germany 122 cancer outpatients of the Comprehensive Cancer Center Munich reported on COVID-19 specific stressors (information satisfaction, threat perception, and fear of disease deterioration) and answered standardized questionnaires for psychosocial distress (DT) as well as depression and anxiety symptoms (PHQ-2, GAD-2). Multiple linear regression analyses were used to identify associations of the COVID-19-related stressors with psychological symptoms, controlling for sociodemographic, psychological (self-efficacy, ASKU) and clinical (somatic symptom burden, SSS-8) variables. Initially, satisfaction with information was significantly negatively associated with all three outcome variables. Fear of disease deterioration was associated with distress and depressive symptoms. After controlling for additional variables, only satisfaction with information remained an independent determinant of anxiety (β = -.35, p < .001). All three outcomes were most strongly determined by somatic symptom burden (β ≥ .40, p < .001). The results of this study tentatively suggest that physical well-being overrides the relevance of some COVID-19-related stressors for oncological patients' psychological wellbeing. Physical symptoms are strongly tied to personal wellbeing as they are associated with suffering from cancer, which might be more central to personal wellbeing than the possibility of getting infected with SARS-CoV-2. However, satisfaction with the information received seems to be important beyond physical wellbeing, as this emerged as an independent determinant of anxiety.